Revolution in paradise : veiled representations of Jewish characters in the cinema of occupied France - Moraly, Jean-Bernard, 1948- (Sussex Academic Press, 2020)
The era of the German Occupation of France constituted, surprisingly, a golden age for the arts: literature, theater, popular music and cinema. These works of art seem to be devoid of political impact. The widespread trend of unrealistic and fantastic art during this period is explained by some scholars as the artists escape from the omnipotent eye of German censorship. The purpose of the book is to show that, contrary to the accepted view, some of these films were intimately linked to the political situation. They convey the demonization of characters that, while not specifically presented as Jews nevertheless manifested anti-Semitic stereotypes of the Jew as ugly, rootless, low, hypocritical, immoral, cruel and power hungry. All five movies analysed (Les Inconnus dans la maison, dir. Henri Decoin, 1942; Les Visiteurs du Soir, dir. Marcel Carne, 1942; L'Eternel retour, dir. Jean Delannoy, 1943; Les Enfants du Paradis, dir. Marcel Carne, 1943) present characters not identified as Jews but who exhibit negative Jewish traits, in contrast to the aristocratic characters whom they aspire to emulate. They demonstrate, implicitly, central themes of explicit anti-Semitic propaganda. Yehuda Moraly addresses two current major misconceptions regarding the Cinema of Occupied France: (1) that the accepted view that there were almost no explicitly Jewish characters in the cinema of that time and place is patently incorrect; and (2) that the feature films of Occupied France were not as it is commonly thought free of the propaganda messages that permeated the press, the radio and documentary films. Analysis of these films brings out the contradictory nature of European anti-Semitism. On one hand, the Jew is the anti-Christ, throttling the world with disgusting materialism while on the other hand, he is representative of an ancestral stifling morality, which it is time to abolish.